Problematika Implementasi Asesmen As, For, Of Learning dalam Pengembangan Pendidikan Agama Islam: Sebuah Kajian Konseptual - Muhammad Zaki Ridho Djakfar; Dwi Ratnasari; Sari Narulita; Suhaeniah Suhaeniah (ALSYS, 2026)
Although assessment in Islamic Religious Education (PAI) learning has an important role in measuring, guiding, and reflecting students’ development, PAI assessment practices still tend to be dominated by conventional tests, so formative and reflective assessment has not been optimally implemented. This article aims to analyze the concepts of assessment as learning, for learning, and of learning in the development of PAI learning through a conceptual study. This study used a literature review method by examining various relevant sources to identify key concepts, critically analyze the weaknesses and opportunities of assessment, and synthesize assessment theory with the contextual needs of Islamic education. The results of the study show that assessment of learning tends to emphasize cognitive achievement, thereby having limitations in assessing students’ affective, psychomotor, and reflective dimensions. Conversely, the integration of assessment for learning and assessment as learning has the potential to become an important strategy in building Islamic character through the processes of feedback, self-reflection, and active student involvement in learning. The conclusion of this study affirms that the ideal PAI assessment model needs to be developed holistically, variatively, and authentically so that it can support the formation of students who are knowledgeable, faithful, and morally upright. These findings contribute to strengthening studies on PAI assessment and provide practical implications for teachers in designing assessments that are oriented not only toward learning outcomes but also toward the process of character formation and students’ religious reflection.